Factors that could influence depositors’ performance at the Lembaga Tabung Haji in Kuala Terengganu / Ahmad Syukri Ismail - Ismail, Ahmad Syukri (2000)
The formation of Lembaga Tabung Haji is one of the ways for the government to attract Muslims who want to perform the Hajj to save. Therefore, the TH in Kuala Terengganu has been a banking institution that has contributed to the development of the finance sector in this state because majority of the people here Muslims. The performance of the depositor at the Terengganu branch has been increasing year by year. This happens because once it was the only one financial institution in the state that operates by the Islamic rules. But there are some other factors that can influence the depositors’ performance. Those are; the staffs’ treatments on customer, service efficiency, office environment, and the product / service offered. With those four factors, I will examine the respondents’ attitude towards those factors in order to identify which factor or factors that could increase the number of depositors to patronize TH. The findings could also reveal which factor or factors that could satisfy depositors’ needs and wants. Some recommendations would be given to enable the TH in Kuala Terengganu to offer quality and accurate service for customer.